Preparation and characterization of new silica-based heterofunctional biocatalysts utilizing low-cost lipase Eversa® Transform 2.0 and evaluation of their catalytic performance in isoamyl esters production from Moringa oleifera Lam oil - Carvalho, Wagner C. A.; Freitas, Rayane A. S.; Barbosa, Milson S.; Paula, Ariela V. [UNESP]; Pereira, Ernandes B.; Mendes, Adriano A.; Franceschi, Elton; Soares, Cleide M. F. (American Institute of Mathematical Sciences (AIMS), 2024)
Due to the need to replace lubricants derived from polluting processes and inputs, bioprocesses and raw materials such as vegetable oils have been used for the production of biolubricants. In this study, the synthesis of esters with lubricating potential was conducted through enzymatic hydroesterification. For complete hydrolysis of Moringa oleifera Lam. seed oil (MOSO), Candida rugosa lipase was applied under conditions already established in the literature. Subsequently, the synthesis of esters of industrial interest was carried out through esterification using a lipase (Eversa Transform 2.0 (ET2.0)) immobilized by different functional groups on heterofunctional silica-based supports: epoxy-silica (Epx), glyoxyl-silica (Gly), and amino-glutaraldehyde-silica (AmG). Two drying pre-treatment techniques were used to improve the immobilization yield of the ET2.0 lipase on different pre-treated supports: evaporation in a drying oven (with improvements ranging from 15% to 46%) and pressure difference in a desiccator (with improvements ranging from 24% to 43%). The immobilizing supports and biocatalysts were characterized to verify their morphologies, structures, and topographies. Deconvolution was performed to evaluate the secondary structure of the ET2.0 lipase and showed increases in the α-helix and β-sheet regions for all biocatalysts after the immobilization process. In a solvent-free medium, the AmG-70h support performed best in the esterification reaction, at around 90% conversion, with a load of 1.65 mg of protein in the reaction. Moreover, it obtained a productivity around 4.45 times that of free ET2.0 lipase, maintaining its original activity until the fourth cycle. This work offers the opportunity to understand and synthesize new biocatalysts with a low-cost genetically modified lipase using a renewable raw material, opening new possibilities to fill gaps that still exist in the use of lipases for biolubricant production.